Wound-Healing Effects of Curcumin and Its Nanoformulations: A Comprehensive Review - Amrita Kumari; Neha Raina; Abhishek Wahi; Khang Wen Goh; Pratibha Sharma; Riya Nagpal; Atul Jain; Long Chiau Ming; Madhu Gupta (MDPI AG, 2022)
Wound healing is an intricate process of tissue repair or remodeling that occurs in response to injury. Plants and plant-derived bioactive constituents are well explored in the treatment of various types of wounds. Curcumin is a natural polyphenolic substance that has been used since ancient times in Ayurveda for its healing properties, as it reduces inflammation and acts on several healing stages. Several research studies for curcumin delivery at the wound site reported the effectiveness of curcumin in eradicating reactive oxygen species and its ability to enhance the deposition of collagen, granulation tissue formation, and finally, expedite wound contraction. Curcumin has been widely investigated for its wound healing potential but its lower solubility and rapid metabolism, in addition to its shorter plasma half-life, have limited its applications in wound healing. As nanotechnology has proven to be an effective technique to accelerate wound healing by stimulating appropriate mobility through various healing phases, curcumin-loaded nanocarriers are used for targeted delivery at the wound sites. This review highlights the potential of curcumin and its nanoformulations, such as liposomes, nanoparticles, and nano-emulsions, etc. in wound healing. This paper emphasizes the numerous biomedical applications of curcumin which collectively prepare a base for its antibiofilm and wound-healing action.